A phytochemical and comparative study to assess the efficacy of Kaidarya (Murraya koenigii (L.) Sprengel) Siddha taila plus Kaidarya vati and Kaidarya vati in Akala palitya (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Regardless of gender, premature hair greying naturally happens in the fourth decade. But these days, it may strike in the early twenties as well. According to Ayurveda faulty eating habits, physical strain, psychological issues, environmental variables, and changes in lifestyle are major reasons which lead to impaired digestion and Pitta dosha vitiation (associated with fire and water element). This mostly leads to loss of hair colour. Present study was phytochemical and interventional study done to assess the efficacy of Kaidarya [Murraya koenigii (L.) Sprengel] siddha taila plus Kaidarya vati and Kaidarya vati alone in Akala palitya. The selection of plant was done on bases of classical lexicons. The group A patients were allotted to Kaidarya siddha taila plus kaidarya vati treatment. The group B patients were only assigned with kaidarya vati. Total enrolled subjects were 95 with respect to dropout rate. The paired t-test was used to analyse the data from Group A and Group B before and after treatment. A noteworthy distinction was noted between the mean values obtained prior to and following the therapy. An independent t-test was used to compare the results between Groups A and B. A significant difference in Akala palitya was found between groups. Group A's mean difference score is higher than Group B's. Therefore, the effect of Kaidarya siddha taila plus kaidarya vati is more than Kaidarya vati in the management of Akala palitya. Furthermore, it requires thorough study, restricted diet and alteration in regimen for more effective results.